Colombia : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Colombia. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights Colombia's favorable outlook, underpinned by the peace agreement, structural tax reform, and the authorities' infrastructure agenda. Economic activity will rebound slightly in 2017 as investment strengthens, boosted by reduced corporate taxation and confidence stemming from the peace agreement. Nontraditional exports are gaining steam thanks in part to ongoing efforts to reduce trade barriers, and this will help bring the current account deficit to its equilibrium level. Medium-term growth will be driven by economic diversification away from oil, which will benefit from the infrastructure agenda, and the peace agreement, which will improve competitiveness and regional development.